A voxel‐based diffusion tensor imaging study in unipolar and bipolar depression. (27th February 2017) - Repple, Jonathan; Meinert, Susanne; Grotegerd, Dominik; Kugel, Harald; Redlich, Ronny; Dohm, Katharina; Zaremba, Dario; Opel, Nils; Buerger, Christian; Förster, Katharina; Nick, Theresa; Arolt, Volker; et al.
Abstract : Objective: The absence of neurobiological diagnostic markers of bipolar disorder (BD) leads to its frequent misdiagnosis as unipolar depression (UD). We investigated if changes in fractional anisotropy (FA) could help to differentiate BD from UD in the state of depression. Methods: Using diffusion tensor imaging (DTI) we employed a voxel‐based analysis approach to examine fractional anisotropy (FA) in 86 patients experiencing an acute major depressive episode according to DSM‐IV (N=39 BD, mean age 39.2 years; N=43 UD, mean age 39.0 years), and 42 healthy controls (HC, mean age 36.1 years). The groups did not differ in sex, age or total education time. FA was investigated in white matter (FA >.2) and hypothesis‐driven anatomically defined tracts (region‐of‐interest [ROI] analysis). Additionally, an exploratory gray matter FA analysis was performed. Results: White matter analysis showed decreased FA in the right corticospinal tract in UD vs HC and in the right corticospinal tract/superior longitudinal fascicle in BD vs HC and also in BD vs UD. ROI analysis revealed decreased FA in BD vs UD in the corpus callosum and in the cingulum. Gray matter exploratory analysis revealed decreased FA in the left middle frontal gyrus and in the right inferior frontal gyrus in UD vs HC, and in the left superior medial gyrus in BD vs HC. Conclusion: This is one of very few studies directly showing differences in FA between BD and UD. Gray matter FA changes in prefrontal areas might be precursors for future prefrontal gray matter abnormalities in these disorders.